The effect of different levels of vitamin E on growth and survivability in juvenile African catfish, Clarias gariepinus - Ramasamy, Seetha (2015)
Vitamin E is an important nutrient influencing fish immune system, reduce mortality and improve fish performance. In the current study, its effect on juvenile African catfish was evaluated by growth and survivability. Eighty juveniles were randomly divided into eight tanks (10 tails/tank) and kept at room temperature (25°c) and pH 7. They were divided into two groups i.e. Group A and B. Both groups were fed with different level of vitamin E incorporated in feed (0, 100, 300, 500 mg/kg) and evaluated by their weight gain within two weeks. Group B was later challenged with A. hydrophila (10^5 cfu/ml) after two weeks and their survivability was observed. Tissue samples from both groups were sent to histopathology. It was shown that in Group A, the average weight gain decreased with increasing dose of vitamin E. In Group B, it was observed that higher mortality was seen in the control group as compared to those fed with the vitamin.